External Shocks, the Real Exchange Rate, and Tax Policy - Tokarick, Stephen (IMF Working Papers; Working Paper ;, 1994)
This paper uses a computable general equilibrium model of the economy of Trinidad and Tobago to assess the effects of trade liberalization and terms-of-trade shocks on the real exchange rate and the overall fiscal position of the government. The model is also used to evaluate the implications of alternative tax policies designed to offset the increase in the budget deficit of the central government that results from both types of external sector shocks.